IMPLEMENTASI TEORI DONALD E. SUPER PADA PROGRAM LAYANAN BK KARIR DI SMK - Maslikhah Maslikhah; Dina Rahmawati Hapsyah; Afan Abdul Jabbar; Dede Rahmat Hidayat (Jurnal Ilmu dan Budaya, 2019)
The implementation of the Donald E. Super vocational education theory is directed towards graduates having professional insight that can affect quality which has four aspects of planning, exploration, informational competence, and decision making. In the age phase of SMK graduates around 18-21 years is a transition period from tentative professional vocational towards specific vocational preferences. Vocational students have characteristics of physical, cognitive, social, emotional, moral, and religious aspects. The career guidance work program at the Vocational School begins with preparation which includes assessing needs, obtaining support from the principal, and establishing the basis for program planning. Preparation of the annual counseling program includes rational, legal basis, vision and mission, description of needs, objectives, program components, service areas, operational plans, theme development, evaluation plans, infrastructure, and cost budgets, Develop activity plans covering competency standard objectives, classes, program components, service strategies, materials, methods, media, evaluation and equivalents.